2018
DOI: 10.1186/s13063-018-2632-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial LED therapy on the cognitive rehabilitation for diffuse axonal injury due to severe acute traumatic brain injury: study protocol for a randomized controlled trial

Abstract: BackgroundPhotobiomodulation describes the use of red or near-infrared light to stimulate or regenerate tissue. It was discovered that near-infrared wavelengths (800–900 nm) and red (600 nm) light-emitting diodes (LED) are able to penetrate through the scalp and skull and have the potential to improve the subnormal cellular activity of compromised brain tissue. Different experimental and clinical studies were performed to test LED therapy for traumatic brain injury (TBI) with promising results. One of the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
8
0
3
Order By: Relevance
“…In the last 20 years, the technology development brought to the market new LEDs, emitting in a broad wavelength range, including the blue region. These compact and low-cost light sources opened up the possibility to design novel light-based therapies, for the treatment of different pathologies, e.g., several different dermatological conditions, brain injuries and spinal cord damages [3][4][5][6][7]. Despite an increasing number of studies regarding the effect of blue light in tissues and cells, the reported information is often incomplete, and it is hard to have a clear and objective comparison of different approaches [5], therefore the underlying mechanism is not deeply understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, the technology development brought to the market new LEDs, emitting in a broad wavelength range, including the blue region. These compact and low-cost light sources opened up the possibility to design novel light-based therapies, for the treatment of different pathologies, e.g., several different dermatological conditions, brain injuries and spinal cord damages [3][4][5][6][7]. Despite an increasing number of studies regarding the effect of blue light in tissues and cells, the reported information is often incomplete, and it is hard to have a clear and objective comparison of different approaches [5], therefore the underlying mechanism is not deeply understood.…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation therapy (PBMT), a treatment method using infrared or near-infrared light (600–1100 nm), is used in traumatic and degenerative brain diseases 11,12 . PBMT (808 nm) irradiation could help cerebrospinal fluid (CSF) to induce neuronal differentiation of human umbilical cord mesenchymal stem cells (hUC-MSCs) in early stage, and can enhance the mesenchymal stem cell (MSC) tissue repair, differentiation and proliferation 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, for w 1118 males exposed to NIR, there were fewer significant changes observed than for females, and gene expression related to “nervous system development” and “neurogenesis” was altered after NIR exposure ( Figure 2B , Table 2 , and Supplementary Data 1 ). Previous studies involving the use of PBM for TBI patients have also reported downregulation of immune response and upregulation of neurogenesis as an effect of NIR treatment ( Hennessy and Hamblin, 2017 ; Santos et al, 2018 ). There was no overlap in biological processes affected across all three TBI time-points shared by both sexes.…”
Section: Resultsmentioning
confidence: 91%
“…Different studies have suggested a positive effect of PBM treatment in TBI patients ( Naeser et al, 2014 ; Poiani et al, 2018 ; Carneiro et al, 2019 ). NIR between 700–1000 nm readily penetrates the scalp and skull and has the potential to improve cellular activity of compromised brain tissue ( Santos et al, 2018 ). Most studies employing NIR treatment have focused on evaluating the efficacy of this exposure on neuropsychological defects like impaired cognition and mood arising from brain injury ( Poiani et al, 2018 ; Santos et al, 2018 ) but none have looked at the effect of NIR on gene transcription.…”
Section: Discussionmentioning
confidence: 99%